Estuaries from a meiofaunal perspective: biodiversity patterns of benthic nematodes - Alves, Ana (2012)
Estuarine meiofauna communities have been only recently considered to be good indicators of ecological quality status, in contrast with macrofauna which is widely used in the assessment and monitoring of aquatic systems. Meiofauna features, such as their small size, high abundance, rapid generation times and absence of a planktonic phase, make these assemblages potential target indicators. In estuaries, we must account not only for great natural variability (e.g. salinity, sediment type and dynamics, oxygen availability, temperature, flow speed) but also for the multiple anthropogenic pressures (high local population density, presence of harbours, dredging activities) that act upon the systems. The meiobenthic community of the Mondego estuary (Portugal) was analyzed, with especial emphasis on the spatial and temporal biodiversity patterns along the entire estuarine gradient. Both taxonomic and functional approaches (density, number of taxa, Margalef and Shannon-Wiener indices, Index of Trophic Diversity and Maturity Index) were applied to nematode communities in order to describe the community structure and to relate it to environmental parameters. The results showed that, at all sampling locations and times, salinity and grain size composition were the main abiotic factors controlling community distribution. Additionally, low temporal variability was observed, which may indicate that natural variability may be superimposed by the anthropogenic pressures present in some areas of the estuary. The integration of both taxonomic and functional attributes proved to be important in assessing the ecological status of estuaries, reinforcing the need to develop a nematode-based multimetric inde